Safety on your bicycle - Raatma, Lucia (Mankato, Minn. : Bridgestone Books, 1999)
Discusses the safety aspects of riding a bicycle, including such topics as helmets, equipment, traffic rules, hand signals, and visibility.
Includes bibliographical references (p. 24) and index.
Keywords: Cycling -- Safety measures -- Juvenile literature; Bicycles -- Safety measures -- Juvenile literature; Bicycles and bicycling -- Safety measures; Safety